2006
DOI: 10.1179/oeh.2006.12.4.400
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception and Communication Regarding Pesticide Use in Rural Work: A Case Study in Rio de Janeiro State, Brazil

Abstract: In an agricultural region of Rio de Janeiro State, Brazil, rapid assessment procedures were used for risk-perception studies based on methodologic triangulation that included semi-structured interviews, participatory observations, and focus groups. Data were qualitatively categorized. Women's risk perception was prioritized, as they did not recognize some risks they were exposed to during work activities. To reach women likely to be exposed to pesticides, a photographic soap opera (fotonovela) was constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 9 publications
3
23
0
8
Order By: Relevance
“…Most of the OP and CM insecticides inhibit the PChE, which is helpful for detecting the early acute effects of poisoning and monitoring the pesticide exposure. Similar results were noted among the tobacco farmers of many other countries (Cornwall et al, 1995;McDaniel et al, 2005;Damalas et al, 2006;Peres et al, 2006;Dasgupta et al, 2007). With an increase in the levels of pesticide residues in blood, there is inhibition of PChE showing lowest levels in the farmers of moderate severity.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Most of the OP and CM insecticides inhibit the PChE, which is helpful for detecting the early acute effects of poisoning and monitoring the pesticide exposure. Similar results were noted among the tobacco farmers of many other countries (Cornwall et al, 1995;McDaniel et al, 2005;Damalas et al, 2006;Peres et al, 2006;Dasgupta et al, 2007). With an increase in the levels of pesticide residues in blood, there is inhibition of PChE showing lowest levels in the farmers of moderate severity.…”
Section: Discussionsupporting
confidence: 80%
“…Indiscriminate use and improper handling of pesticides in agriculture have caused serious health problems in many developing countries, which represent 30% of the global pesticide consumer market (Peres et al, 2006). Organophosphate (OP) and Carbamate (CM) insecticides are commonly used for spraying on the tobacco crops in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…In urban environments, other risk factors of birth defects may prevail, including exposure to other environmental chemicals such as pesticides different than those used in field crops or rural activities. The relationship observed in the rural microregions is of particular concern taking into account that, although agricultural workers in the South and Southeast Region of Brazil might have a higher risk perception from pesticide exposure [31,32] compared to other regions, it has been shown that knowledge and awareness of pesticide risks do not always lead to safety practices among Brazilian farmers [33,34]. Moreover, lower pesticide risk perception has been shown among women in agricultural population in Brazil [20,34], which may lead to a higher pesticide exposure even during pregnancy.…”
Section: Ijomeh 2014;27(3) 482mentioning
confidence: 99%
“…Literature shows that farmers with awareness on the existence of health hazards from using low-quality water perceive such health hazards to be low . Peres and Moreira (2006) emphasized that awareness on the health hazards influence how the hazard is perceived by exposed group. People perceive health hazards when its effects became visible and have a negative perception of the existence of the hazards if there is no observable effect of an exposure.…”
Section: Discussionmentioning
confidence: 99%